Key word signing: Parents' experiences of an unaided form of augmentative and alternative communication (Lámh). (September 2019) - Glacken, Michele; Healy, Denise; Gilrane, Ursula; Gowan, Siobhan Healy-Mc; Dolan, Seamus; Walsh-Gallagher, Dympna; Jennings, Carmel
Parents' experiences of using Lámh, a key word signing approach used in Ireland, were captured through in-depth face-to-face interviews with parents of children with a range of intellectual disabilities. It emerged that Lámh provides child users with one of the rudiments of inclusion, that is, a means of engaging with others. A number of factors can potentially influence the engagement achieved, namely ongoing family commitment to the sustainment of Lámh, available communication partners, accessibility, appropriate Lámh training, speech and language therapy support and the existence of a Lámh signing environment external to the home. The child's family, education and community need to commit to Lámh in order to support a child user become an active member of their community.